Strategic Resonance and Innovation in Public Security Services in Brazil - Menelau, Sueli; Akutsu, Luiz; Isidro Filho, Antonio; Fernandes, Antonio Sergio Araújo (Organizações & Sociedade, 2019)
The aim of this study was to test an exploratory contribution of a model for the relationship between strategic resonance (SR) and innovation in public security services (IPSS), with the construction of two scales. The subject of this analysis are the Federal District Military Police (PMDF) Community Security Stations (CSSs). The model for the relationship was tested using structural equation modeling (SEM) of innovation in public security services (IPSS) and strategic resonance (SR) explanatory variables. The results show that the structural relationships postulated between the variables are corroborated by the global sample analyses, obtaining evidence of scale validation. It was concluded that the CSSs are an IPSS, where it is observed that policing is linked to interactions between the population and PMDF in a relationship comprising the human, structural and operational characteristics of the service. The main contributions of this research are the proposal of a relationship between SR and IPSS and the development and validation of two scales that measure these two constructs.